ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMP PADA MATERI SEGITIGA DAN SEGIEMPAT - Risma Amelia; Usman Aripin; Nurul Hidayani (IKIP Siliwangi, 2018)
This study aims to analyze the creative thinking abilities of junior high school students in the Triangle and Quadrilateral material. The method used in the preliminary study is descriptive qualitative, which aims to analyze the ability of students to solve triangular and quadrilateral problems seen from the level of mathematical creative thinking ability of junior high school students. The population in this study were junior high school students in the city of Cimahi and the sample for this study were 36 eighth grade students in one of the junior high schools in the city of Cimahi. The instrument of creative thinking ability test is given as many as 5 questions with the type of description. Then the results obtained are the level of mathematical creative thinking ability of junior high school students in the city of Cimahi based on the written test is still relatively low.